Pengetahuan Mahasiswa Dan Dosen Terhadap Technopreneurship Di Bidang Fashion - Purnama, Rahayu (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
The development of the industrial revolution 4.0 which will enter industry 5.0 is a challenge andopportunity in facing the future, especially the clothing industry. Apparel industry needtechnopreneur in fashion. Technopreneurship is technology-based entrepreneurship. For this reason,fashion education is expected to increase their knowledge and skills in technology and digitalization.This study aims to determine the knowledge of lecturers and students towards technopreneurship inthe field of fashion. The research was conducted at the Fashion Design Study Program, StateUniversity of Jakarta with 95 respondents of the 2018 and 2019 Undergraduate Fashion Designstudents and the lecturers. The time of the research was carried out in the even semester of 2021.The data collection technique used is a survey using a questionnaire. The data analysis techniquesused in this study are descriptive statistics used to analyze data by describing or describing data thathas been collected as is without intending to make conclusions that apply to the general orgeneralization. The results of this study is lecturers and students' knowledge of technopreneurshipin fashion have an average percentage of almost the same for each sub-indicator, namely thepercentage of autonomy, proactive and aggressive sub-indicators in competition between lecturersand students is equally large. An innovative sub-indicator, the percentage of lecturer knowledge ishigher compared to students. While the percentage of risk-taking sub-indicators, students are higherthan lecturers.